Pemulihan Martabat Manusia dalam Perspektif Metafisika Persahabatan - Yohanes Alfrid Aliano; F.X. Eko Armada Riyanto (Undiksha, 2022)
Human dignity is a special and natural value in the discourse of metaphysical philosophy. The focus of this article is intended to reveal an aspect of the natural values, namely my relationship with God, others, and nature. There is an intimate relationship in the human life that becomes a kind of